Pelatihan Pemasaran Gula Jawa Di Desa Slumbung Kecamatan Ngadiluwih - Ramadhani, Risky Aswi; Helilintar, Risa; Setiawan, Ahmad Bagus; Sanjaya, Ardi; Muzaki, Anwar (Universitas Nusantara PGRI Kediri, 2022)
The people of Slumbung Village, Ngadiluwih sub-district, are mostly sugarcane farmers. They use their land to plant sugar cane, so that the cane is very abundant. Therefore, many people use the sugar cane to be processed into Javanese sugar. Javanese sugar is currently the sugar that is needed by the community in addition to granulated sugar, many benefits can be obtained from brown sugar besides granulated sugar as an alternative to sweeteners in various processed dishes. After conducting several surveys of the people of Slumbung Village, Kec. Ngadiluwih Regency Our Kediri found several obstacles in marketing Javanese Sugar, the first of which was that they only marketed their products to traditional markets. Due to a lack of knowledge about online marketing, it sometimes makes their turnover decrease, even though if they are marketed online this can increase their turnover. The purpose of this PKM is to provide training on how to market products online, using marketplaces and social media, assisting partners until they can actually implement the training they have received.